An analysis of how Zimbabwean female audiences decode meaning from the Shona-language radio programme Nguva Yevanhukadzi (Time for Women) against the background of their lived experiences - Chihota-Charamba, Audrey (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
This study investigates the Zimbabwean women listeners of a gender-focused radio programme Nguva yevanhukadzi (Time for Women) to find out what meanings they take from the programme. Located within the broad theoretical framework of cultural studies and drawing on audience reception theories, the study focuses on the ways in which Shona-speaking women bring their understandings of their social roles, derived from their lived socio-cultural experiences of patriarchy, to their decoding of the text. The study was set in Harare's high-density suburb of Mbare and used the qualitative research methods of individual and focus group interviews. The study was conducted against the backdrop of the signing of the Global Political Agreement (GPA) of September 2008, which ended the impasse among the warring political parties, ZANU PF, MDC-T and MDC and introduced a new era of collectively tackling socio-economic development, including redressing gender disparities through women's empowerment. This study examines the factors shaping the audiences' readings of the programme and seeks to establish whether the mass media has determining power on its audience in the reception of messages or if the audiences (women) have interpretive freedom. Using Hall's (1980) Encoding/ Decoding model, the study examines the factors that influence the audiences' choice in making preferred, negotiated or oppositional readings and the arguments they advance in line with those readings. While the interviews revealed that most of the female listeners "negotiated" the dominant encoded meanings, seeking their relevance to their varied situations and contexts (O' Sullivan et al. 1994:152; Ang 1990: 159), of interest is the manner in which the women dealt with the discourse of patriarchy within the context of promoting women empowerment. The contestation between women empowerment and addressing patriarchy reflected the subverted notions of maintaining the status quo, while applauding the women's commitment and ability to interrogate the practicality of issues under discussion and drawing lessons relevant to their day to day lives prior to making the preferred reading. As such, the study revealed that preferred readings are not always automated, but can be a result of intense interrogation among media audiences.
Keywords: Radio and women -- Zimbabwe; Mass media and women -- Zimbabwe; Radio audiences -- Zimbabwe; Women in mass media; Mass media -- Zimbabwe; Women -- Zimbabwe -- Social conditions; Patriarchy -- Zimbabwe